Three dimensional chemometric analyses of hyperspectral images for beef tenderness forecasting. (January 2016) - Konda Naganathan, Govindarajan; Cluff, Kim; Samal, Ashok; Calkins, Chris R.; Jones, David D.; Meyer, George E.; Subbiah, Jeyamkondan
Abstract: A prototype on-line hyperspectral imaging system (λ = 400–1000  nm ) was developed and used to acquire images of exposed ribeye muscle on hanging beef carcasses (n = 274) at 2-day postmortem in a commercial beef packing plant. After image acquisition, a strip steak was cut from each carcass and vacuum packaged. After aging for 14 days, the steaks were cooked and Warner-Bratzler shear force values were collected as a measure of tenderness. Four different principal component analysis-based dimensionality reduction methods were implemented to reduce information redundancy in beef hyperspectral images. Textural features extracted from the 2-day hyperspectral images were modeled using Fisher's linear discriminant (FLD), support vector machines (SVM), and decision tree (DT) models to predict 14-day aged, cooked beef tenderness. Based on a true validation procedure using 101 samples, the FLD model yielded a tender certification accuracy of 86.7%. In addition, wavelengths corresponding to myoglobin and its derivatives (541, 577, and 635  nm ), beef aging (541, 577, 635, 756, and 980  nm ), protein (910  nm ), fat (928  nm ), and water (739, 756, and 988  nm ) were identified. Highlights: Beef hyperspectral images were acquired on-line. 3-D chemometric methods were developed to analyze beef hyperspectral images. Various textural feature extraction methods and discriminant models were evaluated. Features extracted from 2-day images predicted 14-day beef tenderness. Tenderness certification accuracy of 86.7% was achieved in true validation.